Response of ventrobasal thalamic cells to hair displacement on the face of the waking monkey. - Hayward, J N (1975)
1. In the unanaesthetized, moving monkey, single cell firing patterns in the region of the ventrobasal complex (VB) of the thalamus that respond to facial hair displacement were the basis for a statistical analysis of the effects of tactile, thermal and behavioural stimuli. 2. There were facial hair responses throughout the dorsoventral extent of the ventralis posterior medialis (VPM) nucleus of the contralateral thalamus over a rostro-caudal distance of about 2 mm (Fr. 5.1 to Fr. 7.1). 3. The three different anatomical types of facial hairs that activated thalamic neurones were common facial hairs, circumoral vibrissae and facial whiskers. 4. Displacement of the intermediate length, soft, yellow-brown common facial hairs on the central and lateral face from fields of 1-9 cm2 produced a fast-adapting burst discharge in single thalamic cells in the upper half of the contralateral VPM. 5. Tactile stimuli applied to the short, stiff, white circumoral vibrissae in fields of 0-2-0-9 cm2 along the margins of the upper and lower lips resulted in fast-adapting phasic firing of units in the lower half of the contralateral VPM. Engagement or disengagement of the interlocking hairs of upper and lower lips resulted in increased or decreased, respectively, firing of these thalamic units. 6. Bending a single, long, stiff, black facial whisker extending out from the side of the face resulted in a sustained increased firing of contralateral VPM cells with directional sensitivity. 7. Cells in the ventrobasal thalamus relay mechanoreceptor input from three specialized hair types on the face of the monkey. These somatotopically organized hairy receptive fields are unique, registering response patterns from tactile, thermal and behavioural stimuli. Facial hairs must play an important part in primate feeding, drinking, and oral-exploration.